2016
DOI: 10.1159/000445103
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Galectin-3 Levels Are Increased in Patients with Ischemic Heart Disease, but Are Not Influenced by Acute Myocardial Infarction

Abstract: Objectives: Galectin-3 (Gal-3) is involved in cardiac inflammation and fibrosis, and is in use as a biomarker that indicates increased risk in heart failure. This study examined the relationship between Gal-3 levels and acute and old myocardial infarction (MI) in patients assessed by cardiac magnetic resonance (CMR) imaging. Methods: Group 1 consisted of 38 patients with ST-elevation MI and single-vessel disease treated with primary percutaneous coronary intervention (PCI). Group 2 consisted of 52 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
0
18
1
1
Order By: Relevance
“…Oppositely to above-mentioned findings, Singsaas found only in patients with previous MI, but not in patients with acute STEMI, a significant association between Gal-3 and infarct size or LV volumes, both determinant of adverse LVR after MI and important predictor of adverse cardiovascular events [42]. Thus, in contrast to aforementioned data, they found Gal-3 was useful for risk stratification in patients with previous MI but no acute MI.…”
Section: Gal-3 and Prognosismentioning
confidence: 71%
See 1 more Smart Citation
“…Oppositely to above-mentioned findings, Singsaas found only in patients with previous MI, but not in patients with acute STEMI, a significant association between Gal-3 and infarct size or LV volumes, both determinant of adverse LVR after MI and important predictor of adverse cardiovascular events [42]. Thus, in contrast to aforementioned data, they found Gal-3 was useful for risk stratification in patients with previous MI but no acute MI.…”
Section: Gal-3 and Prognosismentioning
confidence: 71%
“…Clinical Biochemistry 50 (2017) [797][798][799][800][801][802][803] 52 previous complicated MI patients and 22 healthy controls, found Gal-3 levels were increased in both MI groups than controls and it correlated with TnT only in previous MI patients but not in STEMI [42]. Similarly, Lisowska et al in a larger cohort of MI patients including 143 STEMI and 90 NSTEMI patients, found no significant correlation between Gal-3 and TnI on admission [8].…”
Section: Agnello Et Almentioning
confidence: 99%
“…In addition, serum galectin-3 levels varied significantly following a STEMI over a short time period and were associated with the timing of reperfusion ( 75 ). In acute MI, galectin-3 expression levels were positively and significantly associated with certain inflammatory factors ( 76 ), whereas another study demonstrated that galectin-3 expression levels did not change during acute MI and had no association between galectin-3 levels and acute ischemic myocardial injury ( 77 ). In acute MI, galectin-3 was positively and significantly associated with certain biomarkers including matrix metalloproteinase 3, monocyte chemoattractant protein-1, and interleukin (IL)-8 involved in extracellular matrix turnover, but not with LV remodeling ( 78 ).…”
Section: Galectin-3 and Cardiovascular Diseasementioning
confidence: 99%
“…Furthermore, the association between cardiac fibrosis estimated by CMR and Gal-3 levels is not well described. In patients with previous myocardial infarction Gal-3 was moderately associated with LVEF and infarct size [26]. We report no association of the biomarkers Gal-3 with IHD.…”
Section: Discussionmentioning
confidence: 59%